2012
DOI: 10.1001/archneurol.2011.1057
|View full text |Cite
|
Sign up to set email alerts
|

Rebound of Disease Activity After Withdrawal of Fingolimod (FTY720) Treatment

Abstract: Background: The oral sphingosine-1-phosphate receptor modulator fingolimod (FTY720) was recently approved for the treatment of relapsing-remitting multiple sclerosis. To date, data about a possible recurrence of disease activity after discontinuation of fingolimod treatment are scarce. Objective: To describe a patient who discontinued fingolimod treatment after a local malignant melanoma was diagnosed. Three months after cessation, he had a striking rebound of multiple sclerosis activity. Design: Case report a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 11 publications
(8 reference statements)
3
57
0
2
Order By: Relevance
“…In accordance with this, several case reports have described rebound events approximately 2–4 months after stopping FTY 43, 44, 45, 47, 50, 51, 53, 55. Overexpression of sphingosine‐1‐phosphate receptors in entrapped lymphocytes and massive egress of lymphocytes after FTY cessation, observed in animal models, seem to be plausible explanations for such an aggressive disease reactivation in some patients 2.…”
Section: Rebound After Withdrawal Of Fingolimodsupporting
confidence: 67%
See 1 more Smart Citation
“…In accordance with this, several case reports have described rebound events approximately 2–4 months after stopping FTY 43, 44, 45, 47, 50, 51, 53, 55. Overexpression of sphingosine‐1‐phosphate receptors in entrapped lymphocytes and massive egress of lymphocytes after FTY cessation, observed in animal models, seem to be plausible explanations for such an aggressive disease reactivation in some patients 2.…”
Section: Rebound After Withdrawal Of Fingolimodsupporting
confidence: 67%
“…An analysis of >1800 patients who stopped NTZ therapy showed that relapse of disease activity was particularly evident in patients who had had highly active disease before NTZ therapy 42. Similarly, there are some case reports of exacerbation after discontinuation of FTY 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56. Patients with highly active disease before the start of treatment with FTY51 or who showed a good therapeutic response to FTY53 might be predisposed to severe rebound after withdrawal.…”
Section: Rebound After Withdrawal Of Fingolimodmentioning
confidence: 99%
“…The release of lymphocytes after withdrawal of FTY with rapid influx of lymphocytes into the CSF and reconstitution of the immune system has been discussed as reason for MS rebound [Havla et al 2012]. Additionally, whereas B cells in the periphery are strongly reduced they are untouched in the CSF upon treatment with FTY [Kowarik et al 2011].…”
Section: Discussionmentioning
confidence: 99%
“…41 After discontinuation of some drugs, there may be a rapid return or even increase in disease activity compared to baseline, a "rebound effect" as reported for natalizumab, [42][43][44] but also in a single case report for fingolimod. 45 It is has not been rigorously proven that there is a rebound following discontinuation of natalizumab, however; the phenomenon may be represent a return to baseline disease activity following natalizumab cessation, similar to the increase in relapse rates observed following pregnancy. 46 47 There are no reports of recurrent disease activity exceeding pre-treatment baseline after discontinuation of interferon, glatiramer acetate or dimethyl-fumarate.…”
Section: Recurrent Disease Activitymentioning
confidence: 99%